Impacts Of Buddhism in Nepalese Dairy Co-Operatives On Economic Development - Acharya, Sushma (Research Nepal Journal of Development Studies, 2020)
With the kindness, getting milk from animals by natural process with love and care with virtues such as right view, right thought, right speech, right action, right livelihood, right effort, right mindfulness and right concentration could not be misdeed. Buddhists believe that nothing is fixed or permanent. The movement of time and lifestyles for upgrading the production value, People detector improve in sectors, the co-operative concept emerged and is taken as the universal instrument of creating economic miracles by living, thinking and working together to accomplish common goal through cooperative principles. Later on, it gives a huge contribution to global economy. The main theme of the study is how Buddhism and dairy co-operatives eradicates negative consequences from livelihood and plays a vital role on economic development. How it creates right livelihood from a philosophy of noble eightfold path. Buddhists Economics as a new dimension of economic development is developing through dairy cooperatives in Nepal. Objectively, the study is to identify the impacts of dairy cooperatives to economic development of Nepal from Buddhists’ perspective. Methodologically the study is a descriptive qualitative analysis from different secondary information depending upon the reviews of different literature. In conclusion the study found the status of Nepalese dairy cooperatives to generate the opportunities and income determinants to uplift national economy. Buddhism has not any significant impacts on Nepalese diary cooperatives.